UKRAINIAN «I» OF LEONID RUDNYTSKY - Salyga, T. Yu. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In silvertip devoted to 80-th anniversary of birth of well-known Ukrainian literary critic from the USA Leonid Rudnitsky there are question of his life, scientific activity, about his participation in alteration of Ukrainian institutes abroad, in particular UVU (Munich) and SSS in America.